WAQF OF THE BANGSAMORO IN THE PHILIPPINES: ISSUES AND CHALLENGES - Anwar Muhammad Radiamoda (Postgraduate Studies UIN Sulthan Thaha Saifuddin Jambi, 2022)
Waqf, as an Islamic public finance mechanism, can be seen as a tremendous forthcoming instrument that plays a noteworthy role in generating a prominent source of financing for the state and the needs of the multipart and growing Muslims. Waqf is an essential factor of the Islamic economic instruments, which is positively believed, can solve the socio-economic problem mainly in the good challenge to eradicate poverty due to scarcity and insufficiency of income and employment. Although Waqf has been implemented in the Philippines for many years, it has yet to contribute to the welfare of the people today. Thus, this study used a qualitative research method from library research and web-based journals and articles. The literature on the development and management of waqf properties was gathered and reviewed thoroughly. Prior studies provided interesting insight on the importance of Masjid, madrasah, healthcare centers, and integrated schools before the Marawi City war broke up in May 2017. Secondary data on the recent position of the waqf properties in Marawi City has been obtained from the newspaper, Television News Watch, and YouTube. This study tries to discuss issues and challenges facing Muslims during the implementation of Waqf. Therefore this paper proposed a simple action plan that Bangsamoro should take to improve the effectiveness and efficiency of Waqf. In addition, the paper will identify the significant impact of Waqf implementation in the Bangsamoro Autonomous Region in Muslim Mindanao (BARMM) towards generating economic growth in the Provinces of the BARMM. Abstrak: Wakaf, sebagai mekanisme keuangan publik Islam, dapat dilihat sebagai instrumen masa depan yang luar biasa yang memainkan peran penting dalam menghasilkan sumber pembiayaan yang menonjol bagi negara dan kebutuhan umat Islam yang beragam dan berkembang. Wakaf merupakan faktor penting dari instrumen ekonomi Islam, yang diyakini secara positif dapat memecahkan masalah sosial ekonomi terutama dalam tantangan yang baik untuk memberantas kemiskinan akibat kelangkaan dan ketidakcukupan pendapatan dan lapangan kerja. Meskipun Wakaf telah diterapkan di Filipina selama bertahun-tahun, namun hingga saat ini belum memberikan kontribusi bagi kesejahteraan masyarakat. Dengan demikian, penelitian ini menggunakan metode penelitian kualitatif dari penelitian kepustakaan dan jurnal serta artikel berbasis web. Literatur tentang pengembangan dan pengelolaan harta wakaf dikumpulkan dan ditinjau secara menyeluruh. Studi sebelumnya memberikan wawasan menarik tentang pentingnya masjid, madrasah, pusat kesehatan, dan sekolah terpadu sebelum perang Kota Marawi pecah pada Mei 2017. Data sekunder tentang posisi harta benda wakaf di Kota Marawi baru-baru ini diperoleh dari surat kabar, Tontonan Berita Televisi, dan YouTube. Kajian ini mencoba membahas isu dan tantangan yang dihadapi umat Islam selama pelaksanaan wakaf. Oleh karena itu, artikel ini mengusulkan rencana aksi sederhana yang harus diambil Bangsamoro untuk meningkatkan efektivitas dan efisiensi Wakaf. Selain itu, makalah ini akan mengidentifikasi dampak signifikan implementasi Wakaf di Daerah Otonomi Bangsamoro di Muslim Mindanao (BARMM) terhadap pertumbuhan ekonomi di Provinsi BARMM. Kata kunci: wakaf, sosial ekonomi, pengembangan, pengelolaan, administrasi wakaf